Gravimetric determination of soluble phenolics including tannins from leaves by precipitation with trivalent ytterbium - Reed, J.D.; Horvath, P.J.; Allen, M.S.; Soest, P.J. van (Wiley, 1985)
Describes a method for the gravimetric determination of soluble phenolics based on precipitation with trivalent ytterbium; uses some plant species including accacia, albizia, cadaba, euclea, pterolobium and rhus in the analysis.